Analyzing the complications of children with obesity: a systematic review of its effective management based on the latest guidelines - Parikh, Taral; Goti, Ashish; Yashi, Kanica; Kadam, Sandhya; Dihora, Ramesh; Paiwal, Kapil; Parmar, Narendra (International Journal of Contemporary Pediatrics, 2023)
The epidemic of children with obesity has quickly become a significant issue for public health worldwide. Positive energy balance owing to calorie intake exceeding caloric expenditure and a genetic propensity for weight growth is the most prevalent cause of obesity. The goal of evaluating children with obesity is to identify the factors that led to their weight increase and any associated health problems. Children's weight control rests mainly on family-based lifestyle treatments, such as food changes and increased physical activity. A study was conducted to understand and evaluate the measures for effectively managing the complications in children with obesity. The study was carried out based on PRISMA guidelines. The systematic literature search was conducted between 2018 to 2023 from databases such as Medline/PubMed and psych info. Considering the inclusion criteria, 44 articles were included in the present review. The result showed that most of the studies included in this review were conducted on adolescents with obesity aged 5-19 years. Much of the research was a randomized cohort study that focused on the interventions for effective weight management in adolescents. Many studies also included parents and pregnant women as their study subjects. The findings of the studies involved in this review suggested the prognostic factors and different treatment programs that can reduce the consequences of obesity developing into adulthood. Since this is one of the first reviews of its kind, the results might prove helpful in making predictions about potential solutions to the issue of obesity and opening the door to more research into treatment strategies for reducing the adverse impacts of obesity on children.